A geological reconnaissance of the southern part of the Svartenhuk peninsula, West Greenland - Rosenkrantz, Alfred; Noe-Nygaard, Arne; Gry, Helge; Munck, Sole; Laursen, Dan (Meddelelser om Grønland, 1942)
Not applicable.